Comparison of instrumental myofascial release and positional release in patients with asymptomatic lower limb muscle retraction (Research, Society and Development, 2022)
Objective: To compare the difference between instrumental myofascial release and positional release in patients with lower limb muscle retraction. Method: Cross-sectional study of a randomized clinical trial with 35, they were found in tests of retraction of muscles of the lower limbs, it was evaluated and re-evaluated with the goniometer. One group was submitted to Instrumental Myofascial Release performed using polyethylene scrapers and the other to Positional Release manipulations. Descriptive statistical techniques with standard deviation were used, the Kolmogorov-Smirnov test, paired student test, and P value were used. Results: It was found that the techniques of Instrumental Myofascial Release and Positional Release values statistically obtained and reliable values in the improvement of muscle retraction, with a P-value of 0.0001 in both groups and an R Square of 76.31%, about the comparison of techniques, there were no statistically altered differences, a P value of 0.8523, however, in terms of pain complaints, only the instrumental group was observed, reporting pain. Conclusion: The present study found that Instrumental Myofascial Release and Positional Release are effective in improving muscle retraction, but both techniques are statistically similar.